2013
DOI: 10.1063/1.4818171
|View full text |Cite
|
Sign up to set email alerts
|

Ti-catalyzed HfSiO4 formation in HfTiO4 films on SiO2 studied by Z-contrast scanning electron microscopy

Abstract: Hafnon (HfSiO4) as it is initially formed in a partially demixed film of hafnium titanate (HfTiO4) on fused SiO2 is studied by atomic number (Z) contrast high resolution scanning electron microscopy, x-ray diffraction, and Raman spectroscopy and microscopy. The results show exsoluted Ti is the catalyst for hafnon formation by a two-step reaction. Ti first reacts with SiO2 to produce a glassy Ti-silicate. Ti is then replaced by Hf in the silicate to produce HfSiO4. The results suggest this behavior is prototypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The HfTi_PMS_Pr(/Bu) samples show a brighter appearance in contrast to that of the single Hf modified ones, suggesting the formation of a significant amount of hafnon. Previous work on nanolaminated TiO 2 /HfO 2 /HfTiO 4 films (~0.3 μm) on SiO 2 substrate validated that the formation of HfSiO 4 is accelerated in air by the presence of TiO 2 . Moreover it is reported that TiO 2 is formed at 1200°C and at 1500°C for Ti‐alkoxide modified siloxane derived ceramics.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The HfTi_PMS_Pr(/Bu) samples show a brighter appearance in contrast to that of the single Hf modified ones, suggesting the formation of a significant amount of hafnon. Previous work on nanolaminated TiO 2 /HfO 2 /HfTiO 4 films (~0.3 μm) on SiO 2 substrate validated that the formation of HfSiO 4 is accelerated in air by the presence of TiO 2 . Moreover it is reported that TiO 2 is formed at 1200°C and at 1500°C for Ti‐alkoxide modified siloxane derived ceramics.…”
Section: Resultsmentioning
confidence: 88%
“…However, no peaks assigned to residual carbon are visible in the HfTi_PMS_Pr(/Bu) cases, which manifests that no free carbon is present in the SiOC matrix after oxidation. In addition, Raman bands assigned to hafnium silicate, namely hafnon (HfSiO 4 ), are clearly detected in the two Ti‐containing SiOC/HfO 2 nanocomposites after high temperature oxidation. These findings show that the presence of Ti also influences the oxidation process of the SiOC/HfO 2 ceramic nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations